Overcome Limited Efficiency in All‐Perovskite Tandem Solar Cells Upon Light Management at Top Perovskite‐ Transparent Electrode Interfaces - Jinfeng Li; Jinpeng Yang; Xianjie Liu (Advanced Electronic Materials)
Abstract Tandem solar cells have gained significant attention due to their rapid advancements in power conversion efficiency (PCE) and their potential to exceed the detailed balance limit of single‐junction solar cells. However, despite ongoing progress in perovskite‐silicon tandem solar cells, all‐perovskite tandem solar cells (APTSCs) still lag their perovskite‐silicon counterparts. This raises the question: can further development close this gap? Upon theoretical modeling combining optical and electrical calculations, we found that: i) the PCE limitations in APTSCs are primarily caused by the reflection losses at the top perovskite interface; ii) introducing random texturing at the surfaces of wide‐bandgap perovskites plays a critical role in enhancing light absorption, which can potentially improve PCE up to 30.97%. This improvement can be attributed to the reduced reflection and increased absorption at both the top wide‐bandgap and the bottom narrow‐bandgap perovskites. Furthermore, comparison between the calculated results and the experimental data clearly highlights the importance of light management strategies, particularly in improving the short‐circuit current density. This approach is more effective than relying solely on interfacial passivation and energy band alignment to enhance the open‐circuit voltage. The findings will provide valuable theoretical insights for optimizing and advancing the performance of APTSCs.